Keeping them involved: encouraging and monitoring student activity - Williams, Bill (2013)
In the teaching of engineering, lecture classes are often essentially expository with students in a passive role, not preparing learners for autonomous work and this may contribute to high failure and attrition rates. One way to combat this is through the application of Active Learning (AL) methodologies. In this paper results are presented from the application of an AL Methodology in the classroom and outside it for a last year subject of a BEng degree. A Learner Activity Monitoring Matrix has been used to monitoring in-class learner activity. Also described is the implementation of AL outside class using an online learner management system (LMS) which permits voting by students on the quality of solutions proposed by their peers to resolve engineering problems posed by the lecturer. Empirical data regarding the online participation in the process of each learner is provided. A pre-post survey to reveal student perceptions regarding these methodologies is also presented.